The shift to services : a review of the literature - Ronald Schettkat; Lara Yocarini (Institute for the Study of Labor (IZA), 2003)
The present paper provides an overview of literature on the shift to services. It follows the three dimensions of structural change - final demand, the inter-industry division of labor and inter-industry productivity differences. It first looks at the ?classics?, however (Fisher (1935), Clark (1940), Fourastié (1949), Baumol (1967, 2001), and Fuchs (1968)). Next, it treats studies analyzing differences in service-industry employment, and offers a discussion of studies focussing on final demand as an explanation of higher service shares in GDP. It also provides an overview of studies analyzing the inter-industry division of labor on the basis of input-output data. Finally, it discusses studies following Baumol?s cost-disease hypothesis.
Keywords: N1; O4; O3; O1; E2; J3; J2; L8; L0; 330; structural economic change; service industries; economic development; productivity; employment; Dienstleistungssektor; Drei-Sektoren-Hypothese; Strukturwandel; Welt